"... the way we welcome them is how we will lead them to love family planning.": family planning providers in Rwanda foster compassionate relationships with clients despite workplace challenges - Hilary M. Schwandt; Angel Boulware; Julia Corey; Ana Herrera; Ethan Hudler; Claudette Imbabazi; Ilia King; Jessica Linus; Innocent Manzi; Madelyn Merritt; Lyn Mezier; Abigail Miller; et al. (BMC, 2021)
Abstract Background Rwanda has markedly increased the nation's contraceptive use in a short period of time, tripling contraceptive prevalence in just 5 years between 2005 and 2010. An integral aspect of family planning programs is the interactions between family planning providers and clients. This study aims to understand the client-provider relationship in the Rwandan family planning program and to also examine barriers to those relationships. Methods This qualitative study in Rwanda utilized convenience sampling to include eight focus group discussions with family planning providers, both family planning nurses and community health workers, as well as in-depth interviews with 32 experienced modern contraceptive users. Study participants were drawn from the two districts in Rwanda with the highest and lowest modern contraceptive rates, Musanze and Nyamasheke, respectively Data analysis was guided by the thematic content approach, Atlas.ti 8 was utilized for coding the transcripts and collating the coding results, and Microsoft Excel for analyzing the data within code. Results Data analysis revealed that, despite workplace related challenges - including inadequate staffing, training, and resources, relationships between providers and clients are strong. Family planning providers work hard to understand, learn from, and support clients in their initiation and sustained use of contraceptives. Conclusion Given the existing context of purposeful efforts on the part of family planning providers to build relationships with their clients, if the current level of government support for family planning service provision is enhanced, Rwanda will likely sustain many current users of contraception and engage even more Rwandans in contraceptive services in the future.